Polyamide resin composition

By incorporating a fluorine-containing olefin compound into a semi-aromatic polyamide resin composition with bromine-based and metal-salt-based flame retardants, the challenges of achieving balanced flame retardancy, toughness, and flowability in polyamide resin compositions for electrical and electronic components are addressed.

JP7647744B2Active Publication Date: 2025-03-18TOYOBO MC CORP
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2022509951
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-03-25
Filing Date
2021-03-15
Publication Date
2025-03-18
Estimated Expiration
2041-03-15

AI Technical Summary

Technical Problem

Conventional polyamide resin compositions for electrical and electronic components face challenges in achieving a balance between flame retardancy, toughness, mechanical strength, high melting point, low water absorption, bleed-out resistance, and flowability.

Method used

The addition of a specific amount of a fluorine-containing olefin compound to a semi-aromatic polyamide resin composition, which includes a bromine-based flame retardant and a metal-salt-based flame retardant auxiliary, enhances flame retardancy while improving toughness and preventing bleed-out in high-temperature and humidity environments.

Benefits of technology

The resulting polyamide resin composition maintains excellent flame retardancy and mechanical properties, including high melting point and flowability, while minimizing strength reduction and dimensional changes due to water absorption.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007647744000001
    Figure 0007647744000001
Patent Text Reader

Abstract

Provided is a flame-resistant polyamide resin composition which has excellent flame-resistance, toughness, and mechanical strength, which further has a high melting point, low water absorbency, and excellent bleed out resistance and fluidity, and which is suitable for electric / electronic parts. The polyamide resin composition contains a semi-aromatic polyamide resin (A), a brominated flame retardant (B), a metal salt based auxiliary flame retardant (C), and an inorganic reinforcement material (D) in the amounts of 20-67 mass%, 10-40 mass%, 1-15 mass%, and 20-60 mass%, respectively, and is characterized in that: the polyamide resin composition further contains at least one type of fluorine-containing olefin compound (E) selected from the group consisting of ethylene / tetrafluoroethylene copolymer (ETFE), tetrafluoroethylene / hexafluoropropylene copolymer (FEP), and tetrafluoroethylene / propylene copolymer (TFEP), in an amount of 1-10 mass%; and the semi-aromatic polyamide resin (A) contains a structural unit comprising a diamine component and a dicarboxylic acid component that includes terephthalic acid.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a polyamide resin composition which not only has mechanical properties such as high toughness without compromising flame retardancy, but also has a high melting point, does not bleed out in actual use environments such as high temperature and high humidity, is free from strength reduction and dimensional change due to water absorption by the polyamide resin, and exhibits excellent fluidity during molding. [Background technology]

[0002] Taking advantage of their excellent mechanical properties and ease of melt molding, polyamide resins have been widely used in clothing, industrial fiber materials, engineering plastics, etc. In particular, as engineering plastics, they are used in a wide range of applications, including not only automobile parts and industrial machine parts, but also various industrial parts, housing parts, and electrical and electronic parts.

[0003] In recent years, surface mounting methods (flow method, reflow method) have been rapidly spreading in the field of electric and electronic components due to the miniaturization of components accompanying the miniaturization of product size, the high density of mounting, the simplification of processes, and the reduction in costs. In the surface mounting method, the process atmosphere temperature is higher than the solder melting temperature (240 to 260°C), so the resin used is necessarily required to have heat resistance at the above atmosphere temperature. In addition, in the surface mounting process, swelling and deformation of the mounted components due to the resin's water absorption can be a problem, so the resin used is required to have low water absorption. As a resin that satisfies these characteristics, aromatic polyamides such as 6T polyamides are used in surface-mounted electric and electronic components.

[0004] On the other hand, depending on the location and environment in which the molded product is used, it is desirable for the raw material polyamide resin to have flame retardancy based on the UL-94 standard. In response to this need, various proposals have been made to impart flame retardancy to polyamide resin.

[0005] For example, Patent Document 1 describes a technique for making polyamide resin flame-retardant by using a halogenated organic compound such as brominated polystyrene, which is a flame retardant, in combination with antimony trioxide, which acts as a flame retardant assistant. This technique can impart excellent flame retardancy, but since it uses antimony, a heavy metal that is of concern for its effects on the human body, its use in plastic products is gradually being restricted. In addition, antimony trioxide has a problem of lacking stability at the processing temperature of polyamide, which has a high melting point. Therefore, flame-retardant resins using metal salts as a substitute for antimony trioxide have been actively studied. In fact, Patent Document 2 describes an example in which zinc stannate or the like is used as a substitute for antimony trioxide in semi-aromatic polyamide.

[0006] Thus, the use of compounds such as zinc and tin as alternative metals to antimony as flame retardant assistants is becoming more common. However, in order to impart sufficient flame retardancy to polyamide resins, it is necessary to add large amounts of flame retardants and flame retardant assistants, which results in a significant decrease in the mechanical properties of the molded products, such as toughness and mechanical strength.

[0007] As described above, the polyamide resin compositions proposed so far are not satisfactory in terms of flame retardancy, toughness, mechanical strength, high melting point, low water absorption, bleed-out resistance, or flowability, and are currently used despite the problems. [Prior art documents] [Patent documents]

[0008] [Patent Document 1] Japanese Patent Publication No. 1-115956 [Patent Document 2] WO2015 / 056765 publication Summary of the Invention [Problem to be solved by the invention]

[0009] The present invention has been made in view of the above-mentioned current state of the prior art, and an object of the present invention is to provide a flame-retardant polyamide resin composition which is excellent in flame retardancy, toughness, and mechanical strength, and further excellent in high melting point, low water absorbency, bleed-out resistance, and flowability, and is suitable for electric and electronic parts. [Means for solving the problem]

[0010] As a result of intensive research in order to achieve the above-mentioned object, the present inventors have found that by adding a specific amount of a specific fluorine-containing olefin compound to a specific semi-aromatic polyamide resin, in addition to a conventional bromine-based flame retardant and metal salt-based flame retardant auxiliary, it is possible to provide a flame-retardant polyamide resin composition which maintains excellent flame retardancy while significantly improving toughness, is extremely unlikely to cause bleeding on the surface of a molded article under actual usage environments such as high temperature and high humidity, has a high melting point, is excellent in fluidity during molding, and exhibits significantly reduced loss of strength due to water absorption, thereby completing the present invention.

[0011] The present invention has been completed based on the above findings, and comprises the following (1) to (7). (1) A polyamide resin composition comprising a semi-aromatic polyamide resin (A), a bromine-based flame retardant (B), a metal salt-based flame retardant auxiliary (C), and an inorganic reinforcing material (D) in proportions of 20 to 67 mass%, 10 to 40 mass%, 1 to 15 mass%, and 20 to 60 mass%, respectively, wherein the polyamide resin composition is It is an acid-modified ethylene / tetrafluoroethylene copolymer (acid-modified ETFE). A polyamide resin composition further comprising a fluorine-containing olefin compound (E) in an amount of 1 to 10 mass %, wherein the semi-aromatic polyamide resin (A) comprises a structural unit consisting of a dicarboxylic acid component including terephthalic acid and a diamine component. (2) The polyamide resin composition according to (1), further comprising a fluorine-containing elastomer (F), and a mass ratio (E / F) of the fluorine-containing olefin compound (E) to the fluorine-containing elastomer (F) in the polyamide resin composition is 1 to 10. (3) The polyamide resin composition according to (1) or (2), characterized in that the semi-aromatic polyamide resin (A) contains 50 mol % or more of structural units obtained from an equimolar salt of a diamine having 2 to 12 carbon atoms and terephthalic acid, and is obtained by copolymerizing one or more of aminocarboxylic acids having 11 to 18 carbon atoms or lactams having 11 to 18 carbon atoms. (4) The polyamide resin composition according to any one of (1) to (3), characterized in that the semi-aromatic polyamide resin (A) comprises, as constituent components, (a) 50 to 99 mol % of structural units obtained from an equimolar salt of hexamethylenediamine and terephthalic acid, and (b) 1 to 50 mol % of structural units obtained from 11-aminoundecanoic acid or undecane lactam. (5) The polyamide resin composition according to any one of (1) to (4), wherein the mass ratio (B / C) of the bromine-based flame retardant (B) to the metal salt-based flame retardant auxiliary (C) is 1 to 5. (6) An electric / electronic part formed using the polyamide resin composition according to any one of (1) to (5). (7) A housing part formed using the polyamide resin composition according to any one of (1) to (5). Effect of the Invention

[0012] The polyamide resin composition of the present invention not only has mechanical properties such as high toughness without impairing flame retardancy by using a fluorine-containing olefin compound, but also has a high melting point, excellent flowability during molding, and can suppress the formation of bleeding on the surface of molded articles under actual usage environments such as high temperature and high humidity. Furthermore, it can reduce the decrease in strength and dimensional changes caused by water absorption of polyamide resins, making it possible to provide products that highly satisfy user needs. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] The polyamide resin composition of the present invention is suitable for use in electric and electronic devices and electric and electronic components mounted in automobiles and housings of electric devices. The polyamide resin composition of the present invention can be used to form, for example, connectors, switches, housings for ICs and LEDs, sockets, relays, resistors, capacitors, coil bobbins, various housing parts, etc. by injection molding.

[0014] The polyamide resin composition of the present invention contains a semi-aromatic polyamide resin (A), a bromine-based flame retardant (B), a metal salt-based flame retardant auxiliary (C), and an inorganic reinforcing material (D) in amounts of 20 to 67 mass%, 10 to 40 mass%, 1 to 15 mass%, and 20 to 60 mass%, respectively.

[0015] The polyamide resin composition of the present invention is preferably compatible with surface mounting technology, which is a general manufacturing method for electric and electronic components. Therefore, the melting point measured by the method described in the Examples section below is preferably 290 to 350°C. Here, the melting point of the polyamide resin composition refers to the melting peak temperature located at the lowest temperature side among the melting peak temperatures measured by DSC (differential scanning calorimeter) due to the polyamide resin of the polyamide resin composition. The melting point is more preferably 300°C to 340°C, and even more preferably 310 to 340°C. If the melting point exceeds the above upper limit, the processing temperature required when injection molding the polyamide resin composition of the present invention becomes extremely high, so that the polyamide resin composition may be thermally decomposed, and the desired performance and appearance may not be obtained. In addition, if the melting point is less than the above lower limit, the heat resistance in the surface mounting process (230 to 280°C) may be insufficient, which may cause defects such as product deformation during the process.

[0016] With the miniaturization and densification of electric and electronic components, the polyamide resin composition of the present invention is required to stably maintain the strength and product dimensions even after the product absorbs water under the actual usage environment. Therefore, it is preferable that the equilibrium water absorption in water measured by the method described in the Examples section below is 3.0% or less. It is more preferable that the equilibrium water absorption in water is 2.5% or less, and even more preferable that it is 2.0% or less. If the equilibrium water absorption in water exceeds the above upper limit, the strength reduction and dimensional change due to water absorption become significant, and blisters may occur during the reflow soldering process, resulting in problems such as insufficient product strength and assembly failure.

[0017] The semi-aromatic polyamide resin (A) has a constituent unit consisting of a dicarboxylic acid component containing terephthalic acid (TPA) and a diamine component. Examples of the semi-aromatic polyamide (A) include 6T-based polyamides (e.g., polyamide 6T / 6I consisting of terephthalic acid / isophthalic acid / hexamethylenediamine, polyamide 6T / 66 consisting of terephthalic acid / adipic acid / hexamethylenediamine, polyamide 6T / 6I / 66 consisting of terephthalic acid / isophthalic acid / adipic acid / hexamethylenediamine, polyamide 6T / M-5T consisting of terephthalic acid / hexamethylenediamine / 2-methyl-1,5-pent ... Examples of such polyamides include polyamide 6T / 6 made of hexamethylenediamine / ε-caprolactam, polyamide 6T / 4T made of terephthalic acid / hexamethylenediamine / tetramethylenediamine, 9T polyamides (terephthalic acid / 1,9-nonanediamine / 2-methyl-1,8-octanediamine), 10T polyamides (terephthalic acid / 1,10-decanediamine), 12T polyamides (terephthalic acid / 1,12-dodecanediamine), and polyamides made of sebacic acid / paraxylenediamine.

[0018] Among the above-mentioned semi-aromatic polyamides, from the viewpoint of melting point and equilibrium water absorption in water, the semi-aromatic polyamide resin (A) preferably contains 50 mol % or more of constitutional units obtained from an equimolar salt of a diamine having 2 to 12 carbon atoms and terephthalic acid, and is obtained by copolymerizing one or more of aminocarboxylic acids having 11 to 18 carbon atoms or lactams having 11 to 18 carbon atoms. The content of constitutional units obtained from an equimolar salt of a diamine having 2 to 12 carbon atoms and terephthalic acid is more preferably 50 to 98 mol %, and the content of one or more of aminocarboxylic acids having 11 to 18 carbon atoms or lactams having 11 to 18 carbon atoms is more preferably 2 to 50 mol %.

[0019] The diamine component having 2 to 12 carbon atoms constituting the semi-aromatic polyamide resin (A) is preferably an aliphatic diamine having 2 to 12 carbon atoms. Examples of such aliphatic diamine components having 2 to 12 carbon atoms include 1,2-ethylenediamine, 1,3-trimethylenediamine, 1,4-tetramethylenediamine, 1,5-pentamethylenediamine, 2-methyl-1,5-pentamethylenediamine, 1,6-hexamethylenediamine, 1,7-heptamethylenediamine, 1,8-octamethylenediamine, 1,9-nonamethylenediamine, 2-methyl-1,8-octamethylenediamine, 1,10-decamethylenediamine, 1,11-undecamethylenediamine, and 1,12-dodecamethylenediamine, and these may be used alone or in combination.

[0020] The melting point of the semi-aromatic polyamide resin (A) is preferably 290° C. or higher. Considering this point of view, in the case of a semi-aromatic polyamide consisting of a structural unit obtained from an equimolar salt of a diamine having 10 or more carbon atoms and terephthalic acid, the melting point may be 290° C. or lower, so a preferred embodiment is a polyamide resin containing 50 mol % or more of a structural unit obtained from an equimolar salt of a diamine having 2 to 8 carbon atoms and terephthalic acid and having a melting point on the lowest side of 290° C. or higher. If the structural unit obtained from an equimolar salt of a diamine having 2 to 8 carbon atoms and terephthalic acid is less than 50 mol %, the crystallinity and mechanical properties may decrease.

[0021] In the case of a semi-aromatic polyamide consisting of a structural unit obtained from an equimolar salt of a diamine having 6 to 10 carbon atoms and terephthalic acid, by containing 55 mol% or more of this structural unit, it is possible to obtain a polyamide resin having a melting point on the lowest side of 290°C or higher, which is a preferred embodiment. The content of the structural unit obtained from an equimolar salt of a diamine having 6 to 10 carbon atoms and terephthalic acid is more preferably 55 to 98 mol%, and the content of one or more of aminocarboxylic acids or lactams having 11 to 18 carbon atoms is more preferably 2 to 45 mol%. If the content of the structural unit obtained from an equimolar salt of a diamine having 6 to 10 carbon atoms and terephthalic acid is less than 55 mol%, the crystallinity and mechanical properties may decrease.

[0022] Other components can be copolymerized in the semi-aromatic polyamide resin (A) at a molar ratio of 50% or less in the constituent units. Examples of copolymerizable diamine components include aliphatic diamines such as 1,13-tridecamethylenediamine, 1,16-hexadecamethylenediamine, 1,18-octadecamethylenediamine, and 2,2,4 (or 2,4,4)-trimethylhexamethylenediamine, alicyclic diamines such as piperazine, cyclohexanediamine, bis(3-methyl-4-aminohexyl)methane, bis-(4,4'-aminocyclohexyl)methane, and isophoronediamine, and aromatic diamines such as metaxylylenediamine, paraxylylenediamine, paraphenylenediamine, and metaphenylenediamine, and hydrogenated products thereof.

[0023] Examples of the copolymerizable acid component include aromatic dicarboxylic acids such as isophthalic acid, orthophthalic acid, 1,5-naphthalenedicarboxylic acid, 2,6-naphthalenedicarboxylic acid, 4,4'-diphenyldicarboxylic acid, 2,2'-diphenyldicarboxylic acid, 4,4'-diphenyletherdicarboxylic acid, 5-sodium sulfonate isophthalic acid, and 5-hydroxyisophthalic acid; and aliphatic or alicyclic dicarboxylic acids such as fumaric acid, maleic acid, succinic acid, itaconic acid, adipic acid, azelaic acid, sebacic acid, 1,11-undecanedioic acid, 1,12-dodecanedioic acid, 1,14-tetradecanedioic acid, 1,18-octadecanedioic acid, 1,4-cyclohexanedicarboxylic acid, 1,3-cyclohexanedicarboxylic acid, 1,2-cyclohexanedicarboxylic acid, 4-methyl-1,2-cyclohexanedicarboxylic acid, and dimer acid. Copolymerizable components include lactams such as ε-caprolactam, 11-aminoundecanoic acid, undecane lactam, 12-aminododecanoic acid, and 12-lauryllactam, as well as aminocarboxylic acids having ring-opened structures formed by these lactams.

[0024] Among the above components, particularly preferred copolymerization components are, as described above, one or more of aminocarboxylic acids having 11 to 18 carbon atoms or lactams having 11 to 18 carbon atoms. By using aminocarboxylic acids having 11 to 18 carbon atoms or lactams having 11 to 18 carbon atoms, the melting point and heating crystallization temperature can be adjusted to improve moldability, the water absorption rate can be reduced to improve problems caused by changes in physical properties and dimensional changes upon water absorption, and the flowability during melting can be improved by introducing a flexible skeleton.

[0025] When the copolymerization components are composed of a dicarboxylic acid and a diamine, depending on the combination, the melting point may become lower than 290° C., which is not preferable.

[0026] The semi-aromatic polyamide resin (A) is particularly preferably a semi-aromatic polyamide resin having as its constituent components 50 to 99 mol % of a constituent unit obtained from an equimolar salt of (a) hexamethylenediamine and terephthalic acid, and 1 to 50 mol % of a constituent unit obtained from 11-aminoundecanoic acid or undecane lactam. In this case, the semi-aromatic polyamide resin (A) may contain as its constituent components not only the constituent units (a) and (b) but also the constituent units of the above-mentioned copolymerizable components at a ratio of 20 mol % or less. By using a semi-aromatic polyamide (A) having such constituent components, it is possible to realize excellent moldability in addition to a high melting point, low water absorption, and high flowability.

[0027] The semi-aromatic polyamide resin (A) can be produced by a conventional method, and can be easily synthesized, for example, by polycondensation of raw material monomers. The order of polycondensation reaction is not particularly limited, and all raw material monomers may be reacted at once, or some raw material monomers may be reacted first, followed by the remaining raw material monomers. The polymerization method is not particularly limited, and may proceed in a continuous process from raw material charging to polymer production, or an oligomer may be produced once and then polymerized in a separate process using an extruder, or the oligomer may be polymerized by solid-phase polymerization. The ratio of each structural unit in the synthesized copolymerized polyamide can be controlled by adjusting the charging ratio of the raw material monomers.

[0028] Examples of catalysts used in producing the semi-aromatic polyamide resin (A) include phosphoric acid, phosphorous acid, hypophosphorous acid, or their metal salts, ammonium salts, and esters. Specific examples of metal species of metal salts include potassium, sodium, magnesium, vanadium, calcium, zinc, cobalt, manganese, tin, tungsten, germanium, titanium, and antimony. Examples of esters include ethyl ester, isopropyl ester, butyl ester, hexyl ester, isodecyl ester, octadecyl ester, decyl ester, stearyl ester, and phenyl ester. In addition, from the viewpoint of improving melt retention stability, it is preferable to add an alkali compound such as sodium hydroxide, potassium hydroxide, or magnesium hydroxide.

[0029] The relative viscosity (RV) of the semi-aromatic polyamide resin (A) measured in 96% concentrated sulfuric acid at 20° C. is preferably 0.4 to 4.0, more preferably 1.0 to 3.0, and even more preferably 1.5 to 2.5. Methods for adjusting the relative viscosity of the polyamide within a certain range include a method for adjusting the molecular weight.

[0030] The acid value and amine value of the semi-aromatic polyamide resin (A) are preferably 0 to 200 eq / ton and 0 to 100 eq / ton, respectively. If the terminal functional group exceeds 200 eq / ton, not only does gelation and deterioration accelerate during molten retention, but also causes problems such as coloration and hydrolysis in the usage environment. On the other hand, when compounding reactive compounds such as glass fibers and maleic acid-modified polyolefins, it is preferable to set the acid value and / or amine value to 5 to 100 eq / ton in accordance with the reactivity and reactive groups.

[0031] The amount of terminal groups and the molecular weight of the semi-aromatic polyamide resin (A) can be adjusted by a method of polycondensation by adjusting the molar ratio of the amount of amino groups to the amount of carboxyl groups or a method of adding a terminal blocking agent. When polycondensation is performed at a constant molar ratio of the amount of amino groups to the amount of carboxyl groups, it is preferable to adjust the molar ratio of all diamines to all dicarboxylic acids used (diamine / dicarboxylic acid) to a range of 1.00 / 1.10 to 1.10 / 1.00.

[0032] The timing of adding the end-capping agent may include the time of charging the raw materials, the start of polymerization, the later stage of polymerization, or the end of polymerization. The end-capping agent is not particularly limited as long as it is a monofunctional compound that is reactive with the amino group or carboxyl group at the polyamide terminal, and may include monocarboxylic acids or monoamines, acid anhydrides such as phthalic anhydride, monoisocyanates, monoacid halides, monoesters, and monoalcohols. Examples of the end-capping agent include aliphatic monocarboxylic acids such as acetic acid, propionic acid, butyric acid, valeric acid, caproic acid, caprylic acid, lauric acid, tridecanoic acid, myristic acid, palmitic acid, stearic acid, pivalic acid, and isobutyric acid; alicyclic monocarboxylic acids such as cyclohexanecarboxylic acid; aromatic monocarboxylic acids such as benzoic acid, toluic acid, α-naphthalenecarboxylic acid, β-naphthalenecarboxylic acid, methylnaphthalenecarboxylic acid, and phenylacetic acid; acid anhydrides such as maleic anhydride, phthalic anhydride, and hexahydrophthalic anhydride; aliphatic monoamines such as methylamine, ethylamine, propylamine, butylamine, hexylamine, octylamine, decylamine, stearylamine, dimethylamine, diethylamine, dipropylamine, and dibutylamine; alicyclic monoamines such as cyclohexylamine and dicyclohexylamine; and aromatic monoamines such as aniline, toluidine, diphenylamine, and naphthylamine.

[0033] The semi-aromatic polyamide resin (A) must be present in an amount of 20 to 67% by mass, and preferably 25 to 55% by mass, in the entire polyamide resin composition of the present invention. If the amount of the semi-aromatic polyamide resin (A) is less than the lower limit, the mechanical strength will be low, and if it exceeds the upper limit, the amount of other components will be insufficient, making it difficult to obtain the desired effects.

[0034] The brominated flame retardant (B) is blended to impart flame retardancy to the molded article formed from the polyamide resin of the present invention, and must be present in an amount of 10 to 40% by mass in the entire polyamide resin composition of the present invention, and is preferably present in an amount of 13 to 20% by mass. Examples of the brominated flame retardant (B) include tetrabromobisphenol A (TBBA), decabromodiphenyl ether (Deca-BDE), tribromophenol, hexabromocyclododecane (HBCD), ethylene bis(tetrabromophthalimide), TBBA carbonate oligomer, TBBA epoxy oligomer, brominated polystyrene, bis(pentabromophenyl)ethane, TBBA-bis(dibromopropyl ether), poly(dibromophenol), and hexabromobenzene (HBB). In particular, brominated polystyrene is preferred from the viewpoint of stability. Furthermore, the molecular weight of the brominated polystyrene is important for imparting high fluidity to the polyamide resin composition of the present invention during molding, and the weight average molecular weight in terms of standard polystyrene is preferably 4,000 to 8,000, and more preferably 4,000 to 6,000.

[0035] The metal salt-based flame retardant auxiliary (C) is a metal salt or double salt containing Mg, Ca, Sr, Ba, Ti, Mn, Fe, Ni, Cu, Zr, Zn, Mo, Pb, W, Sn, Sb, Bi, Al, etc. as a constituent, and is blended to exhibit high flame retardancy by combining with the bromine-based flame retardant (B). The metal salt-based flame retardant auxiliary (C) must be present in an amount of 1 to 15 mass% in the entire polyamide resin composition of the present invention, and is preferably present in an amount of 2 to 10 mass%. Examples of the metal salt-based flame retardant auxiliary (C) include metal salts mainly composed of zinc stannate, zinc borate, zinc chloride, iron oxide, calcium oxide, boron oxide, aluminum oxide, yttrium oxide, bismuth oxide, molybdenum oxide, zirconium oxide, tin oxide, zinc stannate, zinc hydroxystannate, zinc borate, and calcium borate.

[0036] The total blending ratio of the bromine-based flame retardant (B) and the metal salt-based flame retardant auxiliary (C) in the polyamide resin composition is preferably 11 to 55 mass%, more preferably 15 to 30 mass%. If this total blending ratio is less than the lower limit, the targeted high flame retardancy cannot be obtained, and if it exceeds the upper limit, the physical properties may be significantly reduced and the continuous productivity during compounding may be reduced, which is not preferable. In particular, when using the semi-aromatic polyamide resin (A) selected from the viewpoints of melting point and equilibrium water absorption in water, the blending ratio is important in order to obtain high flame retardancy.

[0037] The blending mass ratio [(B) / (C)] of the bromine-based flame retardant (B) and the metal salt-based flame retardant auxiliary (C) in the polyamide resin composition is important for achieving both high flame retardancy and mechanical properties, and is preferably in the range of 1 to 5. The blending mass ratio [(B) / (C)] is preferably 2 to 4, more preferably 2.5 to 3.5. If this blending mass ratio [(B) / (C)] is out of the above range, it is not preferable because the targeted high flame retardancy and mechanical properties may not be achieved at the same time.

[0038] The inorganic reinforcing material (D) is blended to improve the moldability of the polyamide resin composition and the strength of the molded product, and it is preferable to use at least one selected from fibrous reinforcing materials and needle-shaped reinforcing materials. Examples of fibrous reinforcing materials include glass fibers, carbon fibers, boron fibers, ceramic fibers, and metal fibers. Examples of needle-shaped reinforcing materials include potassium titanate whiskers, aluminum borate whiskers, zinc oxide whiskers, calcium carbonate whiskers, magnesium sulfate whiskers, and wollastonite. As the glass fibers, chopped strands or continuous filament fibers having a length of 0.1 mm to 100 mm can be used. As the cross-sectional shape of the glass fibers, glass fibers having a circular cross section and noncircular cross section can be used. The diameter of the circular cross-section glass fibers is preferably 20 μm or less, more preferably 15 μm or less, and even more preferably 10 μm or less. In addition, glass fibers having a noncircular cross section are preferable from the viewpoint of physical properties and fluidity, but glass fibers having a circular cross section are preferable from the viewpoint of cost. The glass fiber having a non-circular cross section includes those having a substantially elliptical, substantially oval, or substantially cocoon-shaped cross section perpendicular to the longitudinal direction of the fiber, and the flatness is preferably 1.5 to 8. The flatness here is the ratio of the major axis to the minor axis when a rectangle having the minimum area circumscribing the cross section perpendicular to the longitudinal direction of the glass fiber is assumed, and the length of the long side of this rectangle is the major axis and the length of the short side is the minor axis. The thickness of the glass fiber is not particularly limited, but the minor axis is about 1 to 20 μm and the major axis is about 2 to 100 μm. In addition, the glass fiber is preferably used in the form of a fiber bundle cut into a chopped strand shape having a fiber length of about 1 to 20 mm. In order to improve the affinity of the fibrous reinforcing material with the polyamide resin, it is preferable to treat it with an organic agent or a coupling agent, or to use it in combination with a coupling agent during melt compounding. As the coupling agent, any of silane-based coupling agents, titanate-based coupling agents, and aluminum-based coupling agents may be used, with aminosilane coupling agents and epoxysilane coupling agents being particularly preferred.

[0039] The blending ratio of the inorganic reinforcing material (D) in the polyamide resin composition must be 20-60% by mass in order to fully exhibit mechanical properties. This blending ratio is preferably 25-50% by mass, more preferably 30-40% by mass. If the blending ratio is less than the lower limit, the mechanical strength of the molded product may decrease, and if it exceeds the upper limit, extrudability and moldability may decrease, which is not preferable.

[0040] The polyamide resin composition of the present invention is characterized in that it contains a specific fluorine-containing olefin compound (E) as a toughness improver in addition to the above-mentioned components (A), (B), (C), and (D). The blending ratio of the fluorine-containing olefin compound (E) in the polyamide resin composition must be 1 to 10 mass%, and is preferably 1.5 to 9 mass%. If the blending ratio is less than the lower limit, the toughness improving effect is insufficient, and if it exceeds the upper limit, it is not preferable because the mechanical strength and toughness may decrease due to the deterioration of compatibility with the polyamide resin. The fluorine-containing olefin compound (E) used in the present invention is at least one compound selected from the group consisting of ethylene / tetrafluoroethylene copolymer (ETFE), tetrafluoroethylene / hexafluoropropylene copolymer (FEP), and tetrafluoroethylene / propylene copolymer (TFEP). These are preferably acid-modified from the viewpoint of compatibility with polyamide, and modified ETFE is particularly preferable from the viewpoint of toughness improvement. In the present invention, by blending such a specific fluorine-containing olefin compound (E), high toughness can be imparted to the polyamide resin composition without impairing flame retardancy.

[0041] Further, the polyamide resin composition of the present invention may further contain a fluorine-free elastomer (F) in addition to the fluorine-containing olefin compound (E) from the viewpoint of achieving both flame retardancy and toughness. The fluorine-free elastomer (F) can be present in a maximum amount of 6.0 mass% in the entire polyamide resin composition of the present invention. Examples of the fluorine-free elastomer (F) include ethylene / butene copolymer (EBR), ethylene propylene copolymer (EPR), and styrene / ethylene / butylene / styrene copolymer (SEBS). These are preferably acid-modified from the viewpoint of compatibility with polyamide, and modified EBR is particularly preferred from the viewpoint of improving toughness. The blending mass ratio [(E) / (F)] of the fluorine-containing olefin compound (E) to the fluorine-free elastomer (F) in the polyamide resin composition is preferably in the range of 1 to 10 from the above viewpoint. [(E) / (F)] is more preferably 1.5 to 8, and more preferably 1.8 to 5. If this blending mass ratio [(E) / (F)] is outside the above range, it may not be possible to obtain the desired high level of flame retardancy and toughness at the same time.

[0042] From the viewpoint of compatibility with polyamide, the above-mentioned (E) component and (F) component are preferably copolymerized with a reactive group capable of reacting with polyamide. Examples of the reactive group include a group capable of reacting with an amino group, a carboxyl group, and a main chain amide group, which are terminal groups of a polyamide resin. Specific examples include a carboxylic acid group, an acid anhydride group, an epoxy group, an oxazoline group, an amino group, an isocyanate group, etc., and among them, an acid anhydride group has the highest reactivity.

[0043] In addition to the above components (A) to (F), the polyamide resin composition of the present invention may contain various additives used in conventional polyamide resin compositions for electrical and electronic components. Examples of additives include anti-drip agents such as tetrafluoroethylene (PTFE), stabilizers, impact modifiers, release agents, sliding properties modifiers, colorants, plasticizers, crystal nucleating agents, polyamides having compositions different from the semi-aromatic polyamide resin (A), and thermoplastic resins other than polyamides. The possible amounts of these components in the polyamide resin composition are as described below, but the total amount of these components in the polyamide resin composition is preferably 30% by mass or less, more preferably 20% by mass or less, even more preferably 10% by mass or less, and particularly preferably 5% by mass or less.

[0044] The flame-retardant polyamide resin composition of the present invention, by adopting the composition as described above, can not only impart excellent flame retardancy and toughness, but also highly suppress the generation of bleeding on the surface of molded articles under practical use environments, which was observed with the combination of conventional flame retardants, and exhibits fluidity during molding. Furthermore, by using the semi-aromatic polyamide resin (A) characterized by a high melting point and a low equilibrium water absorption in water, a flame-retardant polyamide resin composition having excellent properties such as a high melting point and suppression of deterioration of mechanical properties and dimensional change upon water absorption, in addition to high flame retardancy, can be obtained, making it possible to supply products that highly satisfy user needs.

[0045] The polyamide resin composition of the present invention can be produced by blending the above-mentioned components by a conventionally known method, for example, by adding each component during the polycondensation reaction of the semi-aromatic polyamide resin (A), by dry blending the semi-aromatic polyamide resin (A) with other components, or by melt-kneading each component using a twin-screw extruder.

[0046] The polyamide resin composition of the present invention can be molded by a conventional method such as extrusion molding, injection molding, compression molding, etc. The molded article has excellent flame retardancy and processability and can be used for various applications. Specifically, various electric and electronic parts such as connectors and switches, and housing parts are suitable. The molded article formed using the polyamide resin composition of the present invention is characterized by having both excellent flame retardancy and toughness. EXAMPLES

[0047] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples. The measured values ​​described in the examples were measured by the following methods.

[0048] (1) Relative Viscosity 0.25 g of the polyamide resin was dissolved in 25 ml of 96% sulfuric acid, and the relative viscosity was measured at 20° C. using an Ostwald viscometer.

[0049] (2) Melting point (Tm) Using a Toshiba Machine injection molding machine EC-100, the cylinder temperature was set to the melting point of the resin + 20°C, the mold temperature was set to 35°C, and a test piece for UL combustion test with a length of 127 mm, width of 12.6 mm, and thickness of 0.8 mmt was injection molded to prepare a test piece. In order to measure the melting point (Tm) of the obtained molded product, a part of the molded product was weighed out in an aluminum pan (5 mg) and sealed with an aluminum lid to prepare a measurement sample, and then a differential scanning calorimeter (SEIKO INSTRUMENTS SSC / 5200) was used to increase the temperature from room temperature to the melting point of the resin + 30°C in a nitrogen atmosphere. At that time, the peak top temperature observed on the lowest side of the endothermic peaks due to melting obtained was taken as the melting point (Tm).

[0050] (3) Equilibrium water absorption rate in water Using a Toshiba Machine injection molding machine EC-100, the cylinder temperature was set to the melting point of the resin + 20 ° C, the mold temperature was set to 135 ° C, and a flat plate with a length of 100 mm, a width of 100 mm, and a thickness of 1 mm was injection molded to prepare a test piece for evaluation. The test piece was annealed for 2 hours in an atmosphere of 140 ° C, and then the weight was measured, and the weight at this time was taken as the weight when dried. Furthermore, the annealed test piece was immersed in 80 ° C hot water for 50 hours, and then the weight was measured, and the weight at this time was taken as the weight when saturated with water absorption. The equilibrium water absorption rate in water was calculated from the weights at saturated water absorption and when dry measured by the above-mentioned method using the following formula. Equilibrium water absorption rate in water (%) = {(weight at saturation - weight when dry) / weight when dry} x 100

[0051] (4) Tensile strength retention when absorbing water Using a Toshiba Machine EC-100 injection molding machine, the cylinder temperature was set to the melting point of the resin + 20 ° C, the mold temperature was set to 135 ° C, and the evaluation test pieces were prepared in accordance with ISO 294-1. The prepared test pieces were annealed in an atmosphere of 140 ° C for 2 hours, and then some of them were used to evaluate the tensile properties in accordance with ISO 527-1 and 2. In addition, the remaining test pieces after the annealing treatment were left to stand in an atmosphere of 85 ° C and 85% RH (relative humidity) for 1000 hours, and then the tensile properties were evaluated in accordance with ISO 527-1 and 2. The tensile strength retention rate at the time of water absorption was calculated from the tensile strength after annealing and after saturated water absorption using the following formula. Tensile strength retention rate when absorbing water (%) = (tensile strength after absorbing water saturation / tensile strength after annealing) x 100

[0052] (5) Tensile strength Using a Toshiba Machine EC-100 injection molding machine, the cylinder temperature was set to the resin's melting point + 20°C, the mold temperature was set to 135°C, and evaluation test pieces were prepared in accordance with ISO 527-1 and 2. Using the prepared test pieces, tensile property evaluation was performed in accordance with ISO 527-1 and 2, and the tensile strength was measured.

[0053] (6) Tensile elongation Using a Toshiba Machine EC-100 injection molding machine, the cylinder temperature was set to the resin's melting point + 20°C, the mold temperature was set to 135°C, and evaluation test pieces were prepared in accordance with ISO 527-1 and 2. Using the prepared test pieces, tensile property evaluation was performed in accordance with ISO 527-1 and 2, and the tensile elongation was measured.

[0054] (7) Flame retardancy Using a Toshiba Machine EC-100 injection molding machine, the cylinder temperature was set to the resin's melting point + 20℃, the mold temperature was set to 135℃, and an evaluation test piece measuring 127mm in length, 12.7mm in width, and 0.8mm in thickness was produced by injection molding. Using this test piece, a flame retardancy evaluation was carried out in accordance with the UL-94 vertical flame test.

[0055] (8) MI (Melt Flow Index) In accordance with ISO1133, the fluidity evaluation was carried out with the cylinder temperature set at 330°C and the load set at 2.16 kg.

[0056] (9) Bleed-out resistance Using a Toshiba Machine EC-100 injection molding machine, the cylinder temperature was set to the resin's melting point + 20°C, the mold temperature was set to 135°C, and a flat plate measuring 100 mm in length, 100 mm in width, and 1 mm in thickness was injection molded to create a test specimen for evaluation. This test specimen for evaluation was left to stand for 200 hours in an atmosphere of 80°C and 85% RH (relative humidity), after which the occurrence of bleeding on the surface of the test specimen was visually confirmed according to the following criteria. ○: No bleeding ×: Bleeding occurred

[0057] Synthesis of semi-aromatic polyamide resin (A) As the semi-aromatic polyamide resin (A) used in the examples and comparative examples, the following two types of semi-aromatic polyamide resins (A-1) and (A-2) were synthesized.

[0058] <Synthesis of semi-aromatic polyamide resin (A-1)> 7.54 kg of 1,6-hexamethylenediamine, 10.79 kg of terephthalic acid, 7.04 kg of 11-aminoundecanoic acid, 9 g of sodium hypophosphite as a catalyst, 40 g of acetic acid as a terminal regulator, and 17.52 kg of ion-exchanged water were charged into a 50-liter autoclave, and N was increased from normal pressure to 0.05 MPa. 2 This operation was repeated three times, and the pressure was increased by 1000 psi. 2 After the substitution, the mixture was uniformly dissolved at 135°C and 0.3MPa under stirring. The solution was then continuously supplied by a liquid delivery pump, heated to 240°C by a heating pipe, and heated for 1 hour. The reaction mixture was then supplied to a pressurized reactor and heated to 290°C, and a part of the water was distilled off so as to maintain the internal pressure of the reactor at 3MPa, to obtain a low-order condensate. The low-order condensate was then directly supplied to a twin-screw extruder (screw diameter 37mm, L / D=60) while maintaining the molten state, and polycondensation was carried out under molten conditions while removing water from three vents at a resin temperature of 335°C, to obtain a semi-aromatic polyamide resin (A-1). The obtained semi-aromatic polyamide resin (A) had a relative viscosity of 2.02, a melting point of 315°C, an acid value of 126eq / ton, and an amine value of 22eq / ton.

[0059] <Synthesis of semi-aromatic polyamide resin (A-2)> 7.54 kg of 1,6-hexamethylenediamine, 10.79 kg of terephthalic acid, 7.04 kg of 11-aminoundecanoic acid, 9 g of sodium hypophosphite as a catalyst, 15 g of acetic acid as a terminal regulator, and 17.52 kg of ion-exchanged water were charged into a 50-liter autoclave, and N was increased from normal pressure to 0.05 MPa. 2 This operation was repeated three times, and the pressure was increased by 1000 psi. 2After the substitution, the mixture was uniformly dissolved at 135°C and 0.3MPa under stirring. The solution was then continuously supplied by a liquid delivery pump, heated to 240°C by a heating pipe, and heated for 1 hour. The reaction mixture was then supplied to a pressurized reactor and heated to 290°C, and a part of the water was distilled off so as to maintain the internal pressure of the reactor at 3MPa, to obtain a low-order condensate. The low-order condensate was then directly supplied to a twin-screw extruder (screw diameter 37mm, L / D=60) while maintaining the molten state, and polycondensation was carried out under molten conditions while removing water from three vents at a resin temperature of 335°C, to obtain a semi-aromatic polyamide resin (A-2). The obtained semi-aromatic polyamide resin (A-2) had a relative viscosity of 2.48, a melting point of 315°C, an acid value of 98eq / ton, and an amine value of 34eq / ton.

[0060] Examples 1 to 7, Comparative Examples 1 to 5 The components and mass ratios (parts by mass) shown in Table 1 were melt-kneaded at the melting point of each semi-aromatic polyamide resin raw material +20°C under the following conditions using a twin-screw extruder TEM26SS manufactured by Toshiba Machine Co., Ltd. to obtain polyamide resin compositions of Examples 1 to 7 and Comparative Examples 1 to 5. The polyamide resin compositions of each Example and Comparative Example were used to perform performance evaluations by the above-mentioned method. The results are shown in Table 1. Mixing conditions: Screw rotation speed 200 rpm Discharge amount 20kg / h Glass fiber (GF) is fed from the side feeder, and other raw materials are fed from the Input from infeeder (MF)

[0061] The details of each component listed in Table 1 are as follows. Semi-aromatic polyamide resin (A) Semi-aromatic polyamide resin (A-1) (PA6T / 11 (polyamide 6T / 11), melting point: 315°C, relative viscosity: 2.02, acid value: 126eq / ton, amine value: 22eq / ton) Semi-aromatic polyamide resin (A-2) (PA6T / 11 (polyamide 6T / 11), melting point: 315°C, relative viscosity: 2.48, acid value: 98eq / ton, amine value: 34eq / ton) Brominated flame retardants (B) Brominated polystyrene (SAYTEX® HP-3010PST, manufactured by Albemarle) Metal salt-based flame retardant synergist (C) Zinc stannate (FLAMTARD S (registered trademark) manufactured by Nippon Light Metal Co., Ltd.) Inorganic reinforcement (D) Glass fiber (Nippon Electric Glass Co., Ltd., T-275H, circular cross section) Fluorine-containing olefin compounds (E) Maleic anhydride modified ETFE (Asahi Glass Co., Ltd. FLUON (registered trademark) LM-ETFE AH-2000) Fluorine-free elastomer (F) Maleic anhydride modified EBR (Mitsui Chemicals, Inc., TAFMER® MH7020) Maleic anhydride modified SEBS (Mitsui Chemicals, Inc., TAFMER® M1943) Additives Anti-drip agent: Polytetrafluoroethylene (Daikin Industries, Ltd. Polyflon MPA (registered trademark) FA500H) Talc (Hayashi Kasei KCM7500, particle size 5.8 μm) Release agent: Montan acid ester (CLARIANT LICOLUB(registered trademark) WE 40) Stabilizer: 3,9-Bis{2-[3-(3-tert-butyl-4-hydroxy-5-methylphenyl)propionyloxy]-1,1-dimethylethyl}-2,4,8,10-tetraoxaspiro[5.5]undecane (ADEKA Corporation, Adeka STAB (registered trademark) AO-80)

[0062] [Table 1]

[0063] As is clear from Table 1, by comparing Examples 1 to 3 with Comparative Example 1, it is found that the addition of modified ETFE, which is a fluorine-containing olefin compound (E), not only prevents the decrease in mechanical strength, but also improves toughness and maintains fluidity, and exhibits sufficient flame retardancy. On the other hand, in Comparative Examples 4 and 5, in which modified EBR and modified SEBS, which are fluorine-free elastomers (F), are added instead of the fluorine-containing olefin compound (E), the toughness is improved, but the mechanical strength is clearly reduced, and the flame retardancy is also deteriorated. From Comparative Examples 2 and 3, it is found that the effect of adding this fluorine-containing olefin compound (E) is manifested within a specific range of the amount added. Furthermore, as can be seen from the comparison between Examples 5 and 6, in the system to which the fluorine-containing olefin compound (E) is added, it is not necessary to add an anti-drip agent (PTFE), which is usually required in a halogen flame retardant composition, and it is possible to suppress drip behavior during combustion. In addition, as can be seen from Example 4, the fluorine-containing olefin compound (E) can be used in combination with a fluorine-free elastomer (F), and further improvement in toughness can be achieved by using the fluorine-free elastomer (F) in combination. Note that, as can be seen from Example 7, the above-mentioned effect of the fluorine-containing olefin compound (E) can be similarly achieved even if the amount of the inorganic reinforcing material (D) is changed. [Industrial Applicability]

[0064] The flame-retardant polyamide resin composition of the present invention not only has mechanical properties such as high toughness without impairing flame retardancy by using a fluorine-containing olefin compound, but also has a high melting point, excellent fluidity during molding, and can suppress the formation of bleeding on the surface of molded articles under actual use environments such as high temperature and high humidity. Furthermore, it can reduce the decrease in strength and dimensional changes caused by water absorption of polyamide resins, and molded articles that highly satisfy user needs can be industrially advantageously produced.

Claims

1. A polyamide resin composition containing a semi-aromatic polyamide resin (A), a bromine-based flame retardant (B), a metal salt-based flame retardant auxiliary (C), and an inorganic reinforcing material (D) in proportions of 20 to 67 mass%, 10 to 40 mass%, 1 to 15 mass%, and 20 to 60 mass%, respectively, wherein the polyamide resin composition further contains a fluorine-containing olefin compound (E) which is an acid-modified ethylene / tetrafluoroethylene copolymer (acid-modified ETFE) in a proportion of 1 to 10 mass%, and the semi-aromatic polyamide resin (A) contains a constituent unit consisting of a dicarboxylic acid component containing terephthalic acid and a diamine component.

2. The polyamide resin composition according to claim 1, further comprising a fluorine-containing elastomer (F), and a mass ratio (E / F) of the fluorine-containing olefin compound (E) to the fluorine-containing elastomer (F) in the polyamide resin composition is 1 to 10.

3. The polyamide resin composition according to claim 1 or 2, characterized in that the semi-aromatic polyamide resin (A) contains 50 mol% or more of a structural unit obtained from an equimolar salt of a diamine having 2 to 12 carbon atoms and terephthalic acid, and is copolymerized with one or more of aminocarboxylic acids having 11 to 18 carbon atoms or lactams having 11 to 18 carbon atoms.

4. The polyamide resin composition according to any one of claims 1 to 3, characterized in that the semi-aromatic polyamide resin (A) comprises, as constituent components, (a) 50 to 99 mol % of a constituent unit obtained from an equimolar salt of hexamethylenediamine and terephthalic acid, and (b) 1 to 50 mol % of a constituent unit obtained from 11-aminoundecanoic acid or undecane lactam.

5. 5. The polyamide resin composition according to claim 1, wherein the mass ratio (B / C) of the bromine-based flame retardant (B) to the metal salt-based flame retardant auxiliary (C) is 1-5.

6. 6. An electric / electronic part formed using the polyamide resin composition according to claim 1.

7. A housing part formed from the polyamide resin composition according to any one of claims 1 to 5.

Citation Information

Patent Citations

  • Flame-retardant polyamide resin composition

    JP1989115956A

  • Molding material

    JP1996003438A

  • Flame-retardant polyamide resin composition

    JP1996311333A

  • Flame-retardant polyamide resin composition

    JP1998219103A

  • Polyamide resin composition for pressure housing having explosion-proof property and pressure housing formed by molding the same

    JP2019065285A